INSTITUTIONAL AND VALUE SYSTEM REFORMS IN RA - Gevorgyan, Ruben; Gevorgyan, Gayane (Bulletin of Yerevan University G: Economics, 2019)
The article discusses the need for institutional reforms and changes in the value system to achieve new successes in the socio-economic development of the country. Such reforms are possible only if the possibility of the long existence of inefficient institutions and the ways of their reform are taken into account. It is shown that these reforms are a necessary precondition for all scenarios of socioeconomic transformations in the Republic of Armenia. The article also discusses the features of institutional reforms and changes in the system of values in different sectors of the economy.